2016 IEEE 12th International Conference on Wireless and Mobile Computing, Networking and Communications (WiMob) 2016
DOI: 10.1109/wimob.2016.7763262
|View full text |Cite
|
Sign up to set email alerts
|

User-centric QoE-driven vertical handover framework in heterogeneous wireless networks

Abstract: With the advance of wireless technology and popularity of mobile devices, more and more people rely on mobile devices for multimedia services (such as video streaming and video call). A mobile device can be connected and roamed to different networks in heterogeneous wireless networks. The Media Independent Handover (MIH) framework is designed by IEEE 802.21 group to support seamless vertical handover between different networks. However, how to select an appropriate network from available ones and when to execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The VHO techniques implemented in RF heterogeneous systems have recently been studied. Liu et al [7] proposed a QoE-driven VHO algorithm based on IEEE 802.21-Media Independent Handover (MIH). The simulation results showed that the QoE-driven VHO algorithm could maintain better QoE of a multimedia service by considering video content and initiated VHO immediately when the QoE of the multimedia service became unacceptable.…”
Section: Related Workmentioning
confidence: 99%
“…The VHO techniques implemented in RF heterogeneous systems have recently been studied. Liu et al [7] proposed a QoE-driven VHO algorithm based on IEEE 802.21-Media Independent Handover (MIH). The simulation results showed that the QoE-driven VHO algorithm could maintain better QoE of a multimedia service by considering video content and initiated VHO immediately when the QoE of the multimedia service became unacceptable.…”
Section: Related Workmentioning
confidence: 99%
“…In the existing literature, many studies focus on the development of RAT selection solutions in HetNets such as [2]- [4], and [11]- [20]. RAT selection approaches can be classified as either distributed [2], [4], [11], [14], and [15], or centralised [3], [12], [13], [16]- [20] approaches. With distributed solutions, a wireless device usually gathers performance related measurements from the network before selecting the most suitable RAT according to a specific metric while centralised approaches rely on the global view obtained from the network controller to decide the best RAT.…”
Section: State Of the Art And Paper Contributionsmentioning
confidence: 99%
“…Other studies focus on RAT selection solutions for Het-Nets involving only LTE cells such as macro, femto and picocells [12], [17], and [18]. Finally, the works in [2], [3], [14]- [16], and [19] propose a complete integration between LTE and Wi-Fi going beyond the mere offloading from one network to another.…”
Section: State Of the Art And Paper Contributionsmentioning
confidence: 99%